Lentivirus-mediated silencing of HOTAIR lncRNA restores gefitinib sensitivity by activating Bax/Caspase-3 and suppressing TGF-α/EGFR signaling in lung adenocarcinoma - Liu, Yuanshun (Oncol Lett, 2018)
Secondary resistance is a major limitation in the efficacy of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor treatment of lung cancer. Previous studies have shown that expression of the long non-coding RNA HOX transcript antisense RNA (HOTAIR) is upregulated in lung cancer, which is correlated with metastasis and poor prognosis. However, the precise role of HOTAIR and its effects on gefitinib resistance in human lung adenocarcinoma are not known. To address this issue, in the present study we established a gefitinib-resistant (R)PC-9 human lung adenocarcinoma cell line and examined cell viability with the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium assay. We found that gefitinib concentrations <10 µM inhibited the viability of PC-9 but not RPC-9 cells in a dose-dependent manner. Lentivirus-mediated HOTAIR RNA interference induced cell apoptosis and S-phase arrest, as determined by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling and flow cytometry. Consistent with these observations, HOTAIR suppression was associated with tumor shrinkage and restoration of gefitinib sensitivity in RPC-9 xenograft mice. Immunohistochemical analyses and western blot revealed that HOTAIR silencing resulted in the upregulation of B cell lymphoma 2-associated X protein (Bax), Caspase-3 and transforming growth factor α (TGF-α) and downregulation of EGFR and B cell lymphoma 2 (Bcl-2) levels. These results indicate that HOTAIR normally prevents the activation of Bax/Caspase-3 while inducing TGF-α/EGFR signaling. Thus, targeting HOTAIR may be a novel therapeutic strategy for treating gefitinib-resistant lung adenocarcinoma.